Remote worker communication during COVID-19: The role of quantity, quality, and supervisor expectation-setting. - Shockley, Kristen M.; Allen, Tammy D.; Dodd, Hope; Waiwood, Aashna M. (Journal of Applied Psychology, 2021)
Given the huge increase in remote work that has accompanied the Coronavirus disease (COVID-19) pandemic, understanding predictors of performance and wellbeing among remote workers has never been more timely. Effective communication is commonly cited as key to remote worker success, yet communication variables are rarely incorporated into remote work research. In the present study, we examined the relationship between communication frequency, communication quality, and supervisor-set communication expectations with daily job performance and burnout in an occupationally-diverse sample of employees. We used an experience sampling design and our hypotheses were tested with data collected over a 4-week period with a sample of 471 employees who shifted to full-time remote work due to COVID-19. Results indicated that daily communication quality was associated with daily performance and burnout. In addition, the extent to which supervisors established expectations about communication practices (e.g., expected response times to email) at the onset of the transition to remote work was positively associated with performance, but not burnout. Task interdependence was also tested as a moderator. Task interdependence moderated the relationship between communication quality and performance, such that the relationship was stronger when task interdependence was higher than when it was lower. Task interdependence also moderated the relationship between supervisor-set expectations and performance such that the relationship was stronger when task interdependence was lower than when it was higher. Expected curvilinear relationships between communication frequency and outcomes were not detected. Based on our findings, we provide recommendations for practice and future research. (PsycInfo Database Record (c) 2021 APA, all rights reserved).